2015
DOI: 10.1080/09540121.2015.1109585
|View full text |Cite
|
Sign up to set email alerts
|

Effect of savings-led economic empowerment on HIV preventive practices among orphaned adolescents in rural Uganda: results from the Suubi-Maka randomized experiment

Abstract: Improving economic resources of impoverished youth may alter intentions to engage in sexual risk behaviors by motivating positive future planning to avoid HIV risk and by altering economic contexts contributing to HIV risk. Yet, few studies have examined the effect of economic-strengthening on economic and sexual behaviors of orphaned youth, despite high poverty and high HIV infection in this population. Hierarchal longitudinal regressions were used to examine the effect of a savings-led economic empowerment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 54 publications
1
68
0
Order By: Relevance
“…The Suubi-Maka project followed a similar intervention but extended the treatment groups over 12 and 24 months to include parents to examine family effects on outcomes, which were mixed. While the treatment group reported increased likelihood of the family having saved money (Karimli, Ssewamala, & Neilands, 2014) and an increase in self-reported youth savings (Karimili, 2013), later studies showed no significant effect on the reported amounts saved (Jennings et al, 2016;Karimli et al, 2014) and no significant effect on the use of formal financial institutions (Karimli et al, 2014). Savings attitudes were also found to be weakened by the number of children in the family and significantly affected by family relations, family finance, caregivers' gender, adolescent's gender and educational aspirations (Karimili, 2013).…”
Section: Plural Education With Plural Supportsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Suubi-Maka project followed a similar intervention but extended the treatment groups over 12 and 24 months to include parents to examine family effects on outcomes, which were mixed. While the treatment group reported increased likelihood of the family having saved money (Karimli, Ssewamala, & Neilands, 2014) and an increase in self-reported youth savings (Karimili, 2013), later studies showed no significant effect on the reported amounts saved (Jennings et al, 2016;Karimli et al, 2014) and no significant effect on the use of formal financial institutions (Karimli et al, 2014). Savings attitudes were also found to be weakened by the number of children in the family and significantly affected by family relations, family finance, caregivers' gender, adolescent's gender and educational aspirations (Karimili, 2013).…”
Section: Plural Education With Plural Supportsmentioning
confidence: 99%
“…This study seems to indicate that household conditions may affect individual outcomes for youth. HIV preventative attitudes improved as well as attitudes toward family saving, purchases and vocational training (Jennings et al, 2016).…”
Section: Plural Education With Plural Supportsmentioning
confidence: 99%
“…Findings regarding the impact of the Suubi and Bridges interventions on nonfinancial outcomes have also been very positive. Evidence indicates that a matched savings account combined with financial education and mentoring can have positive impacts on educational outcomes (e.g., standardized test scores, confidence in educational plans), mental health (e.g., depression, hopelessness, self-concept), future orientation, and attitudes about sexual risk-taking (see, e.g., Curley, Ssewamala, and Han;Han, Ssewamala, and Wang, 2013;Kagotho and Ssewamala, 2012;Karimli and Ssewamala, 2015;Jennings, Ssewamala, and Nabunya, 2016;Nabunya and Ssewamala, 2014;Ssewamala, Han, et al, 2010;Ssewamala et al, 2012;Ssewamala, Karimili, Neilands, et al, 2016). Longitudinal research on the Suubi and Bridges interventions continues in Uganda.…”
Section: Cda Experiments In Ugandamentioning
confidence: 99%
“…Results from these matched CSA programs demonstrate a reduction in levels of depression and hopelessness (18); improved HIV preventive attitudes and behaviors (19, 21); improved self-concept and educational achievement (22); and increased financial resources (23, 24). These findings are in line with prior research of transfers (CCT) which have shown positive effects on adolescents (25).…”
Section: Introductionmentioning
confidence: 99%